1994
DOI: 10.1007/bf00194463
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional inflorescence development in Arabidopsis thaliana: Acropetal initiation of flowers and basipetal initiation of paraclades

Abstract: In this study we investigated Arabidopsis thaliana (L.) Heynh. inflorescence development by characterizing morphological changes at the shoot apex during the transition to flowering. Sixteen-hour photoperiods were used to synchronously induce flowering in vegetative plants grown for 30 d in non-inductive 8-h photoperiods. During the first inductive cycle, the shoot apical meristem ceased producing leaf primordia and began to produce flower primordia. The differentiation of paraclades (axillary flowering shoots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
165
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(173 citation statements)
references
References 27 publications
7
165
1
Order By: Relevance
“…This reversion strongly suggests a specific defect in the rosette-to-inflorescence transition in fld-2 mutants. It has been suggested that the early inflorescence phase is the result of the inhibition of vegetative leaf development in wild-type Arabidopsis (Hempel and Feldman, 1994). Therefore, the FLD gene may function as an inhibitory factor to reduce the formation of the vegetative shoot and promote the production of the inflorescence shoot by diminishing COPS activity (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…This reversion strongly suggests a specific defect in the rosette-to-inflorescence transition in fld-2 mutants. It has been suggested that the early inflorescence phase is the result of the inhibition of vegetative leaf development in wild-type Arabidopsis (Hempel and Feldman, 1994). Therefore, the FLD gene may function as an inhibitory factor to reduce the formation of the vegetative shoot and promote the production of the inflorescence shoot by diminishing COPS activity (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its functions in the control of floral organ identity, AP2 has also been shown to control the establishment of flower meristem identity, in part through its interaction with the floral meristem identity gene AP7 (Irish and Sussex, 1990;Bowman et al, 1993;Shannon and Meeks-Wagner, 1993). Strong apl mutants produce highly branched, inflorescence-like flowers that are characterized by the lack of petals, by the replacement of sepals with bractlike leaves, and by the production of ectopic secondary flowers in the axils of the first-whorl leaves (Irish and Sussex, 1990;Bowman et al, 1993;Schultz and Haughn, 1993).…”
Section: Apetala2 (Ap2) Leafy (Lfy) Caullflower (Cal) Termlnal Flomentioning
confidence: 99%
“…Strong apl mutants produce highly branched, inflorescence-like flowers that are characterized by the lack of petals, by the replacement of sepals with bractlike leaves, and by the production of ectopic secondary flowers in the axils of the first-whorl leaves (Irish and Sussex, 1990;Bowman et al, 1993;Schultz and Haughn, 1993). These ectopic secondary or axillary flowers may in turn produce tertiary axillary flowers.…”
Section: Apetala2 (Ap2) Leafy (Lfy) Caullflower (Cal) Termlnal Flomentioning
confidence: 99%
See 2 more Smart Citations